Pengaruh Tingkat Pemahaman Agama Islam dan Perhatian Orangtua terhadap Hasil Belajar Pendidikan Agama Islam dan Budi Pekerti di SDN14 Sungai Aur - Yusmira Hayati; Sulaiman Sulaiman (FONDATIA, 2022)
This study aims firstly to find out how the influence of understanding Islam on learning outcomes of Islamic Religious Education and Morals, secondly to find out how the influence of parental attention on learning outcomes of Islamic Religious Education and Morals, then to find out how the influence of understanding of Islam and people's attention parents together on the learning outcomes of Islamic Religious Education and Character Education. This research method uses associative quantitative. In taking the sample, the researcher used purposive sampling method. The research instrument used is a questionnaire as a data collection tool. While the analysis technique used is quantitative associative analysis using multiple linear regression hypothesis testing, coefficient of determination test, simple regression coefficient test and Simultaneous test. The results of the study found that there was an influence of the variable understanding of Islam on learning outcomes of Islamic Religious Education and manners for class IVA of .59.7 or 59.7% and for class IVB of .31.0 or 31%. Meanwhile, the variable of parents' attention to the learning outcomes of Islamic Religious Education and Morals for class IVA is .506 or 50.6% and for class IVB it is .88,0 or 88%. Then there is a joint effect of the variable understanding of Islam and parental attention for class IVA of .91.9 or 91.9% and for class IVB of .93.0 or 93%. It can be concluded that there is an influence of the variable understanding of Islamic Religion on the learning outcomes of Islamic Religious Education and Morals, there is an influence of parental attention on the learning outcomes of Islamic Religious Education and Character and there is an influence of understanding Islamic Religion and parental attention together on learning Education Islam and good manners for grades IVA and IVB at SDN 14 Sungai Aur.